PARTICIPATORY ACTION RESEARCH FOR DEVELOPMENT OF A CURRICULUM FOR ENHANCING DESIRABLE CHARACTERISTICS OF “DEKDEE SRIWERNCHAI IN A SUFFICIENCY WAY” FOR ELEMENTARY SCHOOL STUDENTS AT BAN SRIWERNCHAI SCHOOL UNDER NAKHON PHANOM PRIMARY EDUCATION SERVICE AREA OFFICE 2 - Chonburee, Santhit; Chomphunuch, Phattanan; Noinon, Puntarika (Journal of MCU Nakhondhat, 2025)
This research aimed to 1) Study the conditions, problems, and needs of stakeholders and teachers at Ban Sriwenchai School regarding the development of a curriculum, 2) Develop a curriculum for enhancing desirable characteristics of “Dekdee Sriwernchai in A Sufficiency Way.”, and 3) Study the resulfs of the implementation of the developed curriculum. Using a participatory action research process with 6 steps. The target group consists 9 administrators, teachers from Ban Sriwenchai School, and 38 stakeholders. Quantitative data were analyzed using percentage, mean, and standard deviation, while Qualitative data were analyzed using content analysis. The findings revealed that: 1) The school lacks a curriculum related to the sufficiency economy or local wisdom philosophy. Students were found to lack desirable characteristics. Both teachers and stakeholders expressed a strong need to develop a supplementary curriculum that instills such values in students. 2) The curriculum for enhancing desirable characteristics consisted of eight components and was rated at the highest level of appropriateness. and 3) The trial implementation of the curriculum showed that: 3.1) Students demonstrated desirable characteristics at a level exceeding the 70% benchmark. 3.2) The evaluation results of the curriculum using the CIPP model: Context, schools, and communities need curricula to enhance desirable characteristics. Input is appropriate for students. Process, the curriculum was appropriate. Products, Students’ desirable characteristics under the theme significantly improved. and 3.3) Administrators, Teachers, stakeholders, and students expressed the highest satisfaction with the curriculum.